Modelled nitrogen and sulfur deposition over Europe 1980-2011 - Bennet, Cecilia (SMHI - Swedish Meteorological and Hydrological Institute, 2021)
The Eulerian Transport and Chemistry model MATCH (Robertson et al. 1999) has been used to estimate the deposition over Europe from 1980 to 2011. In data to the model is meteorology from ERA-Interim (Dee et al. 2011) and emissions from EMEP (The European Monitor and Evaluation Programme, http://www.ceip.at/webdeb-emission-database). The MATCH model has been set up with 22 vertical layers and the top height is 6 km. The thickness of the lowest layer is 20 m. Results of the modelled nitrate deposition over Sweden have been published in the IVL-report “Trender i kvävenedfall över Sverige 1955-2011” (Hansen et al. 2013 in Swedish). The available data are modelled gridded data, for the years 1980-2011, of the diurnal mean atmospheric concentrations in the lowest model layer, and dry and wet deposition of: ammonium nitrate (NH4NO3), other nitrate, ammonium sulfate ((NH4)2SO4), other sulfate, NO, NO2, SO2 and ozone (O3). The netcdf-files also includes gridpoint latitude and longitude.
A sample of the data are available here for year 1980. The full dataset can be obtained by contacting the Principal investigator.
References:
Dee, D. P., Uppala, S. M., Simmons, A. J., Berrisford, P., Poli, P., Kobayashi, S., … Vitart, F. (2011). The ERA-Interim reanalysis: configuration and performance of the data assimilation system. Quarterly Journal of the Royal Meteorological Society, 137(656), 553–597. https://doi.org/10.1002/qj.828
Robertson, L., Langner, J., & Engardt, M. (1999). An Eulerian Limited-Area Atmospheric Transport Model. Journal of Applied Meteorology, 38(2), 190–210. https://doi.org/10.1175/1520-0450(1999)038<0190:aelaat>2.0.co;2.

Den eulerianska transport- och kemimodellen MATCH (Robertson et al. 1999) har använts för att uppskatta avsättning över Europa från 1980 till 2011. Data omfattar meteorologi från ERA-Interim (Dee et al. 2011) och utsläpp från EMEP (The European Monitor and Evaluation Programme, http://www.ceip.at/webdeb-emission-database). En MATCH-modell sattes upp med 22 vertikala lager och med en maximal höjd på 6 km. Tjockleken på det lägsta lagret är 20 m. Resultatet från modellerat nitratnedfall över Sverige har publicerats i IVL-rapporten “Trender i kvävenedfall över Sverige 1955-2011” (Hansen et al. 2013). Data utgörs av modellerat rutnät för åren 1980-2011, för dagliga atmosfäriska medelkoncentrationer i det nedersta modellagret, och torr- samt våtdeposition av: ammoniumnitrat (NH4NO3), andra nitrater, ammoniumsulfat ((NH4)2SO4), andra sulfater, NO, NO2, SO2 och ozon (O3). FIlerna innehåller också longitud/latitud för varje ruta i rutnäten.
Här tillhandahålls data för året 1980. Hela datasetet kan återfås genom att kontakta ansvarig forskare.
Referenser:
Dee, D. P., Uppala, S. M., Simmons, A. J., Berrisford, P., Poli, P., Kobayashi, S., … Vitart, F. (2011). The ERA-Interim reanalysis: configuration and performance of the data assimilation system. Quarterly Journal of the Royal Meteorological Society, 137(656), 553-597. https://doi.org/10.1002/qj.828
Robertson, L., Langner, J., & Engardt, M. (1999). An Eulerian Limited-Area Atmospheric Transport Model. Journal of Applied Meteorology, 38(2), 190-210. https://doi.org/10.1175/1520-0450(1999)038<0190:aelaat>2.0.co;2.
Modellerade kväve och svavelnedfall över Europa 1980-2011
Keywords: Ammonium Sulfate; Ammoniumsulfat; SULFATE; deposition; deponering; air sulfate concentration; sulfate; sulfate deposition; ammonium nitrate; ammoniumnitrat; nitrates; nitrater; Environment and conservation; Miljö och naturvård; Environmental Sciences; Miljövetenskap; Meteorology and Atmospheric Sciences; Meteorologi och atmosfärsvetenskap; Elevation; Höjddata; Climatology / Meteorology / Atmosphere; Klimatologi och meteorologi; Environment; Miljö